Pharmacotherapy only? Overview of available treatments for sleep disorders - Górska, Karolina; Antoniak-Sobczak, Katarzyna; Ścisło, Lucyna; Pluta, Judyta; Pluta, Mateusz; Buczkowska, Marta; Górski, Michał K. (Nursing Problems / Problemy Pielęgniarstwa, 2024)
Sleep disorders are one of the most common disorders of human well-being. They cause numerous health consequences, such as attention disorders, memory and recall difficulties, and motor disorders. The diagnosis of sleep disorders and the selection of the appropriate form of treatment is essential for helping patients. Current medicine offers many therapeutic options using pharmaco-logical and non-pharmacological methods. During the treatment process, it is advisable to make changes in life hygiene and some-times pharmacological support is necessary. This article reviews the available treatments for sleep disorders and provides a brief description of each. Aspects of sleep hygiene, relaxation training, psychotherapy, biofeedback, non-invasive brain stimulation methods, and the basic groups of drugs used in treatment, e.g. antidepressants, neuroleptics, benzodiazepines, and non-benzodiazepine GABA receptor agonists, are included.